Guía para la identificación genérica de larvas de quironómidos (diptera: chironomidae) de la Sabana de Bogotá. III. subfamilias tanypodinae, podonominae y diamesinae (2000)
A diagnosis of larvae in the subfamilies Tanypodinae and Podonominae (Chironomidae) is provided, based on macroscopic and microscopic characters. A key to the genera recorded in streams of the Sabana de Bogotá and surrounding mountains is presented. Additionally, diagnoses are given for the genera Podonomus and Parochlus of the subfamily Podonominae and the genus araheptagyia, of the subfamily Diamesinae.